A compact ultra-wideband bandstop filter using mu-negative and ENZ metamaterial resonators for multiple advanced wireless communication systems - Mouhssine Elbathaoui; Nawfal Jebbor; Sudipta Das; Wael Ali; Sahaya Anselin Nisha Arockiam; Om Prakash Kumar; El-Mahjoub Boufounas (PLoS ONE, 2025)
A compact ultra-wideband bandstop filter (UWB-BSF) based on a microstrip line and innovative complementary electrical LC (CELC)-loaded metamaterial (MTM) resonators is proposed. These MTM resonators exhibit negative effective permeability and epsilon-near-zero (ENZ) effective permittivity. The design employs a Rogers RO3006™ substrate and achieves an ultra-wide 3-dB stopband extending from 5.4 GHz to 21.6 GHz, equivalent to a fractional bandwidth of 120%, with a high rejection level. The shape factor (SF = 0.87), close to 1, and seven transmission zeros indicate high selectivity in the transition bands. The group delay remains flat in the lower and upper passbands, with GD ≤ 0.74 ns and GD ≤ 0.50 ns, respectively. The suggested UWB-BSF, with an overall size of 0.55λg × 2.22λg × 0.07λg, has been validated through simulations and measurements. The results demonstrate significant selectivity in the transition bands, making the filter particularly suitable for modern technologies such as 5G (Sub-6 GHz) and 5G NR (New Radio), especially within the n77 (3.3–4.2 GHz), n78 (3.3–3.8 GHz), and n79 (4.4–5.0 GHz) frequency bands, as well as Wi-Fi 5 (802.11ac), Wi-Fi 6 (802.11ax), 4G LTE, Ku-band satellite communications and K-band radar systems, by enhancing precision through effective mitigation of undesired signals. This research supports SDG 9, SDG 11, and SDG 12 by fostering innovation in wireless communication infrastructure, enabling sustainable smart city applications, and promoting efficient, compact design practices.